A Linguistic Error Analysis of ESL Written Essays by Indian Tamil University Students - Asteria Gabriel Ngaiza (Journal of Modern Research in English Language Studies)
Although many ESL university students know grammar rules, most cannot write competently. Meanwhile, effective writing would affect students’ overall academic performance. This article examined the written errors of the Indian Tamil learners of English as their Second Language (ESL). The study adopted a cross-sectional research design and collected data through written essays. The participants were studying Master of Arts in English second-year integrated class. The participants were purposely selected. The study assessed errors as they occurred in students’ written essays. Data were descriptively analysed in which they were categorised based on the themes. The findings showed several errors, categorised as subject-verb errors, word order patterns, spelling errors, and omissions. Findings have depicted error cases in word order errors, unnecessary insertion, misplaced inversion and sentence fragment errors. The results have shown that some students made apparent errors that could be termed as negligent ones, while others could be associated with transfer from the first language. In addition, other errors are associated with the way the English language is taught. Based on the results, this study recommends that ESL teachers should focus their teaching on these problematic areas and provide the students with many writing tasks that would improve the writing of the Tamilians, whose English is their second language.